2012
DOI: 10.1016/j.watres.2011.12.059
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of virus on iron-oxide coated sand: Enhancing inactivation in sunlit waters

Abstract: The goals of this study were to investigate the release of infective bacteriophages MS2 and FX174 (two human viral indicators) after adsorption onto an iron oxide coated sand (IOCS), and to promote viral inactivation by exploiting the photoreactive properties of the IOCS.The iron oxide coating greatly enhanced viral adsorption (adsorption densities up to w10 9 infective viruses/g IOCS) onto the sand, but had no affect on infectivity. Viruses that were adsorbed onto IOCS under control conditions (pH 7.5, 10 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…The same action has been recorded when disinfection is referred to bacterial populations [21]. However, based on our results and in accordance to other studies, photocatalysis proved to be effective method for wastewater disinfection in artificial and natural conditions [6,27]. Additional asset of this technique is the fact that it may contribute in reducing the precursors responsible for the formation of disinfection by-products (DBPs), which are often produced, especially if wastewater disinfection practice involves chlorination [27].…”
Section: Natural Sunlight-mediated Phages Inactivationsupporting
confidence: 87%
See 1 more Smart Citation
“…The same action has been recorded when disinfection is referred to bacterial populations [21]. However, based on our results and in accordance to other studies, photocatalysis proved to be effective method for wastewater disinfection in artificial and natural conditions [6,27]. Additional asset of this technique is the fact that it may contribute in reducing the precursors responsible for the formation of disinfection by-products (DBPs), which are often produced, especially if wastewater disinfection practice involves chlorination [27].…”
Section: Natural Sunlight-mediated Phages Inactivationsupporting
confidence: 87%
“…However, it should be noted that the solar irradiation alone, without the addition of any catalyst, reduced the amount of colony forming endospores causing detrimental damages to the cells [13]. In the case of MS2 phages, the resistant nature of the virus requires significant high periods, which in certain cases may reach 24 h in order to observe a 4 Log decay with sunlight exposure [6]. Apart from the light intensity dependence, there are other factors that may differentiate the course of the process, of which the composition is enlisted among the most determinants.…”
Section: Natural Sunlight-mediated Phages Inactivationmentioning
confidence: 99%
“…This is due mainly to the unique properties of viruses, such as their small size making them difficult to filter (~20-90 nm), as well as their increased resistance too many disinfection techniques that are routinely used to kill other pathogens. Because of these challenges, there is greater focus on developing more sophisticated methods for removing viruses from water [19][20][21][22]. Virus filtration is generally reliable for virus removal, but there are many issues to consider when designing a novel retention filter.…”
Section: Separation Filtration and Affinity Recognition Of Virusesmentioning
confidence: 99%
“…In addition, semiconductor photocatalysis was also suggested as an efficient technology for disinfection of water and wastewater (Robertson et al, 2012). Moreover, Pecson et al (2012) demonstrated that iron oxide coated sand enhanced the separation of viruses from the water column, and additionally provided a photocatalytic mechanism to promote inactivation of viruses in constructed wetlands.…”
Section: Biological Agentsmentioning
confidence: 99%